Ethyl 4-[3,5-bis(trifluoromethyl)phenyl]-6-methyl-2-oxo-1,2,3,4-tetrahydropyrimidine-5-carboxylate - Hoong-Kun Fun; Ching Kheng Quah; M. Babu; B. Kalluraya (Acta Crystallographica Section E, 2009)
In the title compound, C16H14F6N2O3, the dihydropyrimidinone ring adopts an envelope conformation. In the crystal, molecules are linked by N—H...O and C—H...O hydrogen bonds into a ribbon-like structure along the b axis. In the ribbon, a pair of bifurcated acceptor N—H...O and C—H...O bonds generate an R21(6) ring motif. Adjacent ribbons are linked via C—H...F hydrogen bonds.